2005
DOI: 10.1175/jhm-400.1
|View full text |Cite
|
Sign up to set email alerts
|

The Catastrophic Flash-Flood Event of 8–9 September 2002 in the Gard Region, France: A First Case Study for the Cévennes–Vivarais Mediterranean Hydrometeorological Observatory

Abstract: International audienceThe Cévennes–Vivarais Mediterranean Hydrometeorological Observatory (OHM-CV) is a research initiative aimed at improving the understanding and modeling of the Mediterranean intense rain events that frequently result in devastating flash floods in southern France. A primary objective is to bring together the skills of meteorologists and hydrologists, modelers and instrumentalists, researchers and practitioners, to cope with these rather unpredictable events. In line with previously publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
259
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 365 publications
(267 citation statements)
references
References 26 publications
4
259
0
4
Order By: Relevance
“…The MCS stayed over the same region for about 24 hours, leading to surface rainfall totals reaching very extreme values (Figure 4(b)): 691 mm in 24 hours was recorded in the Gard region. This flooding resulted in more than 20 fatalities (Delrieu et al, 2005).…”
Section: Gard Case: 8-9 September 2002mentioning
confidence: 99%
“…The MCS stayed over the same region for about 24 hours, leading to surface rainfall totals reaching very extreme values (Figure 4(b)): 691 mm in 24 hours was recorded in the Gard region. This flooding resulted in more than 20 fatalities (Delrieu et al, 2005).…”
Section: Gard Case: 8-9 September 2002mentioning
confidence: 99%
“…The flow peaks are reached within a few hours, thus giving little or no advance warning to mitigate flood damage (Borga et al, 2007;Borga et al, 2008). This hydrological response leads to the occurrence of a typology of floods known as flash floods because of their rapid onset, i.e., within six hours of rainfall (Ogden et al, 2000;Delrieu et al, 2005;Marchi et al, 2010;Hapuarachchi et al, 2011;Naulin et al, 2013;Ballesteros-Canovas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Distributed hydrological models show significant improvements after including the local aspect of precipitation (Michaud and Sorooshian, 1994;Zoccatelli et al, 2010); and in particular, an increase in the likelihood criterion (Nash-Sutcliffe) of up to 30% (Zoccatelli et al, 2010). Studying the particular case of the flash-flood event of 8-9 September 2002 in the Gard region, Anquetin et al (2010) and Delrieu et al (2005) found that the distribution of the spatial forcing particularly influences the flood dynamic when it interacts with the spatial distribution of the soil properties before saturation.…”
Section: Introductionmentioning
confidence: 99%